2021
DOI: 10.1039/d1ra00275a
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of nitric oxide (NO) in neuroblastoma treatment

Abstract: S-Nitrosoglutathione (GSNO) reduces cell viability, inhibits cell division, and induces cell cycle arrest and apoptosis in neuroblastoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Herein, the novel combination of NO, delivered via S-Nitrosoglutathione (GSNO) (Figure 1a), and SMYD3 inhibition, with inhibitor-4 (Figure 1b), is investigated for anticancer potential against breast cancers. In previous studies, the RSNO, GSNO, was shown to exhibit tumoricidal characteristics [30][31][32]. Likewise, a separate study indicated that a SYMD3 inhibitor, inhibitor-4, demonstrated potent impacts on two breast cancer lines, MCF7 and MDA-MB-231 (both lines linked to overexpression of SMYD3) [29].…”
Section: Introductionmentioning
confidence: 91%
“…Herein, the novel combination of NO, delivered via S-Nitrosoglutathione (GSNO) (Figure 1a), and SMYD3 inhibition, with inhibitor-4 (Figure 1b), is investigated for anticancer potential against breast cancers. In previous studies, the RSNO, GSNO, was shown to exhibit tumoricidal characteristics [30][31][32]. Likewise, a separate study indicated that a SYMD3 inhibitor, inhibitor-4, demonstrated potent impacts on two breast cancer lines, MCF7 and MDA-MB-231 (both lines linked to overexpression of SMYD3) [29].…”
Section: Introductionmentioning
confidence: 91%
“…Nitric oxide ( • N = O, abbreviated NO), despite its structural simplicity, is an important free radical biomolecule with complex chemistry, which has a crucial role in several physiological and biological functions, e.g., the prevention of oxidative stress and cytokine activation, neurotransmission, and vascular homeostasis [ 1 ]. NO-based therapies exhibit great potential as antimicrobials and antivirals in the acceleration of wound healing and anticancer treatment [ 2 , 3 , 4 , 5 ]. More recently, the potential of inhaled NO was also explored in COVID-19 treatment, since it can stabilize oxidation stress, which is the major cause of comorbidity deaths [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, researchers have developed a variety of exogenous NO donors, including thionitrosothiols, metal nitric oxide complexes, polyamines, diazendioates, etc., which respond to various stimuli and specifically release NO to reduce systemic toxicity. [9][10][11][12][13] For instance, Fang et al loaded DOX and a NO donor (S-nitrosothiol) into mesoporous silica (MSN) to construct DN@MSN nanoparticles. The results showed that the loaded NO donor can activate matrix metalloproteinases (MMPs), enhance the penetration and accumulation of DN@MSN and DOX in tumors, thereby significantly improving the antitumor efficacy.…”
Section: Introductionmentioning
confidence: 99%